CONTRASTING ARBOREAL AND TERRESTRIAL BRYOPHYTES COMMUNITIES OF THE MOUNT HALIMUN SALAK NATIONAL PARK, WEST JAVA - NUNIK S. ARIYANTI; SULISTIJORINI SULISTIJORINI (BIOTROPIA, 2011)
Bryophyte communities were compared between arboreal (trunk bases) and terrestrialhabitats in primary forest Mount Halimun Salak National Park, West Java. The communitieswere analyzed based on species diversity, abundance, and biomass. A total of 150 bryophytesspecies were identified, including 67 species of mosses (Bryopsida) and 83 of liverworts(Hepaticopsida). Both bryophyte groups varied in diversity and abundance between arborealand terrestrial communities as well as among different elevations. Species diversity of arborealhabitats (116 species)was higher than that of terrestrial habitats (64 species). Moss speciesweremore abundant in terms of coverage in terrestrial habitats whereas liverworts species weremore abundant in arboreal habitats. Species richness in both terrestrial and arboreal habitatsdecreased towards higher elevation, whereas the abundance increased.